A novel method for suppressing phase retrieval error caused by scanning based on amplitude correlative in-situ matching. (May 2022) - Liu, Xu; Liu, Yong; Jiang, Hongzhen; Li, Dong; Chen, Zu; Ren, Huan; Chai, Liqun; Zhu, Qihua; Zheng, Wanguo; Tan, Qiaofeng
Highlights: We then propose a correction method for correcting two-dimensional (2D) scanning deviations based on an amplitude correlative in-situ matching technique, which can adequately overcome the grid phase distortion caused by the motion error of the 2D scanning system. We design a method for measuring the optical plate wavefront based on the extended ptychographic method for measuring wavefront of the optical plate in high-power laser systems. The experimental results show that the grid phase distortion caused by position error can be suppressed effectively using the proposed correction method. Abstract: Aiming at satisfying the requirements in detecting the wavefront of the optical plate in high-power laser systems, in this study we design a method for measuring the optical plate wavefront based on the extended ptychographic method. We then propose a correction method for correcting two-dimensional (2D) scanning deviations based on an amplitude correlative in-situ matching technique, which can adequately overcome the grid phase distortion caused by the motion error of the 2D scanning system. Moreover, the accuracy of the proposed correction method was validated via simulation. A step optical plate with a diameter of 100 mm and a bee wing were measured using the proposed method. The experimental results show that the grid phase distortion caused by position error can be suppressed effectively using the proposed correction method.